Community Participation in Urban Sanitation Programs at Koja, Jakarta, Indonesia - Angga Dheta Shirajjudin Aji; Sapta Suhardono; Evi Siti Sofiyah; Betanti Ridhosari; Almira Davina Nastiti; Wisnu Prayogo; I Wayan Koko Suryawan (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Urban sanitation remains a critical public health issue, with community participation recognized as a key factor in the success of sanitation programs. This study aims to explore the multi-dimensional factors influencing community participation in the urban setting of Koja. Through a mixed-methods approach, including surveys, interviews, and observational studies, we investigated how socio-demographic factors such as age, gender, income, and occupation, as well as aspects of sanitation governance, infrastructure, and educational interventions, interplay to affect community engagement. The study revealed that while infrastructure and access are crucial, socio-economic and gender-related barriers significantly impact participation levels. Educational level emerged as a strong predictor of engagement, indicating that awareness and knowledge play a critical role in motivating community involvement. Furthermore, sanitation governance and the quality of policies and monitoring were found to be instrumental in shaping public attitudes towards participation. The research highlights the necessity for integrated and inclusive sanitation policies that address the local context and socio-economic diversity of urban populations. The findings underscore the importance of targeted educational campaigns and the fostering of collaborative community relationships to enhance participation in sanitation programs. This study contributes to the discourse on urban sanitation by providing a nuanced understanding of the complex factors at play in community-based sanitation efforts, offering insights for policymakers to improve public health outcomes.